Oduzimanje imovinske koristi pribavljene učinjenjem krivičnog djela / Confiscation of Property Obtained through Criminal Activities - Katica, Damir (Pregled: časopis za društvena pitanja / Periodical for social issues, 2023)
The confiscation of the property obtained through criminal activities is a very important consequence of criminal conviction. In this way, it is told to potential offenders that they will not be able to maintain the property benefits obtained by criminal actions, and in such a way, it is also implemented both special and general prevention. The goal of revoking property acquired in a illegal way is not only preventive and punitive, but also to protect the interests of the injured party. The main task of each state is to focus on the confiscation of the property, to create defense mechanisms in the fight against organized crime and to implement a financial investigation with the aim of identifying, seized and subtracting the assets that arose to do severe crimes, and all This is a strategic plan for the fight against organized and difficult crime.